Glycosylation and cross-linkage of cardiac myosin in diabetic subjects: a post-mortem study - Yudkin, J S; Cooper, M B; Gould, B J; Oughton, J (Diabetic medicine, 1988)
We have investigated the possibility that post-translational modification of myosin by protein glycosylation and cross-linking occurs in cardiac myosin. Left ventricular muscle was obtained at post-mortem from 6 diabetic and 7 non-diabetic subjects. Myosin was extracted from muscle and purified using Sephadex chromatography followed by protein concentration. Glycosylation was estimated using boronate affinity chromatography with the myosin dissolved in a pyrophosphate buffer, the glycosylated myosin being displaced with sorbitol. Cross-linkage was assessed by fluorescence at 440 nm upon excitation at 370 nm. Diabetic subjects had significantly higher levels (p less than 0.02) of glycosylated myosin (median 6.0% (range 3.8-6.6%] than non-diabetic subjects (median 2.4% (range 0.3-4.2%] but there was no difference in the degree of cross-linkage as assessed by fluorescence (diabetic median 9.8 (range 6.5-17.0) arbitrary units; non-diabetic median 9.7 (range 6.0-11.4) arbitrary units). Glycosylation of left ventricular myosin may be of relevance to the excess risk of congestive cardiac failure in diabetic patients.